Factors affecting water demand: macro evidence in Malaysia - Zuraini Anang,; Jaharudin Padli,; Noorhaslinda Kulub Abdul Rashid,; Roseliza Mat Alipiah,; Haslina Musa, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Water becomes a crucial issue in the 21st century because of rising population and increasing development. Water is needed for agriculture, energy production, recreation, and manufacturing. This study investigates the impact of economic indicators and climate change on water demand for 13 states in Malaysia. Using annual data from 2007 to 2015, the panel data approach is used to assess the impact of these determinants on water demand. The dependent variable is water resources, and independent variables comprise real income, total consumption per capita, agriculture sector, population density and climate change. The real income is a nonlinear equation and indicates a threshold in economic development because the welfare of residents and industry will decline after the optimum point due to the shortage of water resources. The results indicate that total consumption per capita, agriculture, and population density have a positive impact on water demand. The agriculture sector exerts high demand on water resources. The climate change is a correct sign that represents an increase in demand for water resources during dry periods and leading to water stress. This finding is useful for improving the prediction of climate change to managing the water resources sustainably, particularly in the agriculture sector.